Reliability and validity of a reactive agility test for Australian football - Veale, J. P.; Pearce, A.; Carlson, J. S. (International Journal of Sports Physiology and Performance, 2010)
Purpose: The aim of this study was to test the reliability and construct validity of a reactive agility test (RAT), designed for Australian Football (AF). Methods: Study I tested the reliability of the RAT, with 20 elite junior AF players (17.44 ± 0.55 y) completing the test on two occasions separated by 1 wk. Study II tested its construct validity by comparing the performance of 60 participants (16.60 ± 0.50 y) spread over three aged-matched population groups: 20 athletes participating in a State Under-18 AF league who had represented their state at national competitions (elite), 20 athletes participating in the same league who had not represented their state (subelite), and 20 healthy males who did not play AF (controls). Results: Test-retest reliability reported a strong correlation (0.91), with no significant difference (P = .22) between the mean results (1.74 ± 0.07 s and 1.76 ± 0.07 s) obtained (split 2+3). Nonparametric tests (Kruskal-Wallis and Mann-Whitney) revealed both AF groups performed significantly faster on all measures than the control group (ranging from P = .001 to .005), with significant differences also reported between the two AF groups (ranging from P = .001 to .046). Stepwise discriminant analyses found total time discriminated between the groups, correctly classifying 75% of the participants. Conclusions: The RAT used within this study demonstrates evidence of reliability and construct validity. It further suggests the ability of a reactive component within agility test designs to discriminate among athletes of different competition levels, highlighting its importance within training activities.